2019
DOI: 10.3390/nu11092201
|View full text |Cite
|
Sign up to set email alerts
|

Non-Nutritive (Artificial) Sweetener Knowledge among University Students

Abstract: This study determined non-nutritive sweetener (NNS; artificial sweetener) depth of knowledge among university health and science students. An online survey was delivered to 1248 science students and completed by 493 respondents (19.0 ± 2.2 years old), evaluating ability to provide an NNS description/definition, examples of NNS from memory, and evaluate NNS word familiarity with a click-drag-box to identify six NNS by chemical name (CN) and six NNS by trade name (TN), relative to six decoy NNS, six caloric swee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This may have a negative public health impact. Studies have suggested that even young adults, who are usually more health-conscious/literate than other age groups, may not realize that they have consumed NNSs/LCSs [18,44]. Furthermore, patients with phenylketonuria (PKU) need to avoid products containing aspartame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have a negative public health impact. Studies have suggested that even young adults, who are usually more health-conscious/literate than other age groups, may not realize that they have consumed NNSs/LCSs [18,44]. Furthermore, patients with phenylketonuria (PKU) need to avoid products containing aspartame.…”
Section: Discussionmentioning
confidence: 99%
“…Co-presence of NNSs/LCSs with free sugar has also become more common [11]. This could be a potential public health concern considering nutrition labels are not required to display the amount of NNSs/LCSs used [15][16][17], and therefore, consumers may be unaware that some sugars in their favorite foods/beverages are being replaced by NNSs/LCSs [18].…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Wilson et al in 2019 [ 31 ], parents are unlikely to even know what NNS are. Thus, they are mostly unaware of the presence of NNS in foods and do not regulate the amount of intake by their kids.…”
Section: Discussionmentioning
confidence: 99%
“…However, the unwitting consumer just sees "agave" on the ingredients list and may assume the product is healthier than a product listing sugar as an ingredient. Recent research has underscored that chemical or alternative names for sugars found on ingredient labels is not always helpful for consumers; 30-50% of them, when surveyed, incorrectly identified sucrose, fructose, and dextrose as being non-caloric sweeteners [33]. [34] and the Public Health England Composition of Foods Integrated Dataset [35].…”
Section: Common Sources Of Sugar and Marketingmentioning
confidence: 99%